Mirror women, surrealism, and images: self-representation - Chadwick, Whitney; Ades, Dawn; MIT List Visual Arts Center.; Miami Art Museum.; San Francisco Museum of Modern Art. (MIT Press, 1998)
During the 1930s and 1940s, women artists associated with the Surrealist movement produced a significant body of self-images that have no equivalent among the works of their male colleagues. While male artists exalted Woman's otherness in fetishized images, women artists explored their own subjective worlds. The self-images of Claude Cahun, Dorothea Tanning, Leonora Carrington, Frida Kahlo, Meret Oppenheim, Remedios Varo, Kay Sage and others both internalize and challenge conventions for representing femininity, the female body, and female subjectivity. Many of the representational strategies employed by these pioneers continue to resonate in the work of contemporary women artists. The words "Surrealist" and "surrealism" appear frequently in discussions of such contemporary artists as Louise Bourgeois, Ana Mendieta, Cindy Sherman, Francesca Woodman, Kiki Smith, Dorothy Cross, Michiko Kon and Paula Santigo. This book, which accompanies an exhibition organized by the MIT List Visual Art Center, explores specific aspects of the relationship between historic and contemporary work in the context of Surrealism. The contributors re-examine art historical assumptions about gender, identity, and integenerational legacies within modernist and postmodernist frameworks. Questions raised include: how did women in both groups draw from their experiences of gender and sexuality? What do contemporary artistic practices involving the use of body images owe to the earlier examples of both female and male Surrealists? What is the relationship between self-image and self-knowledge. (source: Nielsen Book Data)
Keywords: 1900-1999; 1930-1939; 1940-1949; 1970-1979; 1980-1989; 1990-1999; approches et analyses; arts; arts visuels et médiatiques; cours; discipline; har4600; histoire de l'art; modernisme; postmodernisme; premier cycle; périodes historiques; sexualité; thématiques

Femmes peintres: 1550-1950 - Harris, Ann Sutherland; Nochlin, Linda (Ed. des femmes, 1981)
Catalogue d'exposition. Il s'agit de la première exposition rassemblant les oeuvres de femmes peintres, organisée au Los Angeles Country Museum of Art par Ann Sutherland Harris, conservateur au Metropolitan Museum of Art de New York et Linda Nochlin, enseignante en histoire de l'art à l'université de Vassar. Ces oeuvres jusque-là dispersées dans divers musées et collections privées, et rassemblées dans cette exposition et ce catalogue devenu un ouvrage de référence, font apparaître la place des femmes et leur influence parfois marquante dans l'histoire de l'art occidental. D'Italie en Flandres, en France, en Allemagne, en URSS, aux États-Unis, la vie et l'oeuvre de : Catherina Van Hemessen, Sofonisba Anguissola, Fede Galizia, Judith Leyster, Clara Peeters, Élisabeth Vigée Le Brun, Rosa Bonheur, Sonia Delaunay... Et bien d'autres.
Keywords: 1500-1599; 1600-1699; 1700-1799; 1800-1899; 1900-1909; 1900-1999; 1910-1919; 1920-1929; 1930-1939; 1940-1949; amérique du nord; amériques; arts; arts visuels et médiatiques; cours; discipline; europe; femmes* artistes; har4600; histoire de l'art; histoire et politique; incontournable; peinture; premier cycle; périodes historiques; régions géographiques; thématiques